IMPLEMENTASI PENDEKATAN TARL TERHADAP PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA MATERI GAYA KELAS IV SDN KARANGREJO 04 SUMBERSARI JEMBER - Nadia Puspitasari; Isrorul Wahidah; Fajar Surya Hutama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of the implementation of the TaRL approach to improving the learning outcomes of students in the style material of grade IV SDN Karangrejo 04 Sumbersari Jember. This type of research is classroom action research (CAR) with a model design according to Kurt Lewi's opinion with the steps of planning, acting, observing, and reflecting. The subjects of the study were grade IV students in the 2024/2025 academic year with a total of 28 students. The data collection instrument used in the study was a learning outcome test on the style material. This study was carried out for 2 cycles where each cycle consisted of 2 meetings and 1 assessment. Data was processed in each cycle and then percentage analysis was carried out. Where the learning outcomes in the activities (pre-cycle) were 32% or 9 out of 28 students were still in the completed category, then in cycle 1 there was an increase of 61% and in cycle 2 there was a more significant increase to 82%. So it is known that the increase in the percentage of completion from cycle 1 and cycle 2 was 21%. Based on the results of this study, it can be concluded that the implementation of Teaching at The Right Level (TaRL) can improve the learning outcomes of grade IV students of SDN Karangrejo 04 Sumbersari Jember on the material on force.